PENGARUH PEMBERIAN GULA AREN TERHADAP KUALITAS NATA DE LERI SEBAGAI RANCANGAN LKPD MATERI PELAJARAN BIOTEKNOLOGI TINGKAT SMA KELAS XII - Wenny Anggraini; Darmawati Darmawati; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to determine the effect of giving palm sugar to the quality of nata de leri as a design 3rd grade of senior high school biotechnology subject material in February-March 2019. The research carried out in two stages, namely the experimental stage: the effect of giving palm sugar on the quality of nata de leri and the second stage the design of the LKPD:the analysis of potential development of class XII high school biotechnology subject. The research used the experimental method by conducting experiments at the Laboratory of the Faculty of Mathematics and Natural Sciences (FMIPA), Pekanbaru. Sampling was carried out with a completely randomized design (CRD) consisting of 5 treatments and 3 replications. The parameters in this research were thickness analysis, acidity analysis (pH), and organoleptic test. Based on the results of Analysis of Variance (ANOVA) at the level of 5%, administration of palm sugar showed a significant effect on the quality of nata de leri. giving 200 grams of palm sugar gives the best improvement to the quality of nata de leri and based on the analysis of potential research results it can be used as a design for Student Worksheet (LKPD) for grade XII high school biotechnology subject material.Key Words: Quality of the Nata de leri, LKPD design, Palm sugar